IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM BENTUK UPAYA MENINGKATKAN KEPEDULIAN SISWA SMP MUHAMMADIYAH 3 TERHADAP LINGKUNGAN SEKITAR MELALUI SEMINAR LINGKUNGAN - Septiana, Tina; Yulianti, Siska Dwi; Fauziyah, Siti Sarah; Susanto, Eko (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Garbage is the remains of human daily activities or natural processes in solid or semi-solid form in the form of organic or inorganic substances that are biodegradable or non-biodegradable which are considered useless and disposed of into the environment. As representatives of the future society, students must be equipped with the value of caring for the environment from an early age. This community service program uses the lecture and question and answer method in the form of a seminar with the theme